2015
DOI: 10.5799/ahinjs.02.2015.01.0166
|View full text |Cite
|
Sign up to set email alerts
|

A nosocomial outbreak of Crimean-Congo hemorrhagic fever

Abstract: ABSCRACTObjectives: An outbreak of nosocomial Crimean-Congo Hemorrhagic Fever (CCHF) occurred in a university hospital in May 2014. The index case was hospitalized with a preliminary diagnosis of intoxication, liver failure and disseminated intravascular coagulopathy (DIC). The index case, a farmer, died a few hours later with signs of bleeding.Outbreak Investigation: Crimean-Congo Hemorrhagic Fever Polymerase Chain Reaction (PCR) was positive in the index case serum. RT-PCR and/or IgM serology were reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(58 reference statements)
0
7
0
2
Order By: Relevance
“…LVD responds well to the broad-spectrum antiviral agent ribavirin [ 33 ], while it has been suggested that ribavirin could be useful in the treatment of the South American arenaviral infections [ 62 ] and Crimean Congo haemorrhagic fever [ 63 , 64 ]. However, the latter has not been confirmed and is controversial [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…LVD responds well to the broad-spectrum antiviral agent ribavirin [ 33 ], while it has been suggested that ribavirin could be useful in the treatment of the South American arenaviral infections [ 62 ] and Crimean Congo haemorrhagic fever [ 63 , 64 ]. However, the latter has not been confirmed and is controversial [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes were classified using a strict case definition: all confirmed HCW cases had positive serology (IgM or IgG seroconversion) and/or positive PCR results. Thirteen of the cases identified have been reported in two previous publications [8] , [9] . Asymptomatic cases were confirmed by CCHF IgG seroconversion.…”
mentioning
confidence: 95%
“…Healthcare personnel are at risk from occupational infections during patient care; the first such cases were described in Pakistan and were later reported from many Eurasian countries [4] , [5] , [6] , [7] , [8] , [9] . Isolated imported cases of CCHF or outbreaks in countries lacking CCHF experience present particular infection control challenges, increased risk to healthcare workers (HCWs), and are associated with increased mortality [6] .…”
mentioning
confidence: 99%
“…Following the first cases reported in Pakistan, cases were reported with regard to health services throughout the Middle East. [9][10][11][12] Our country is endemic in terms of CCHF, but in countries where cases are rarely seen, health personnel face an increased risk. [8] These injuries lead to psychiatric problems as much as physical ones that may occur after trauma.…”
Section: Introductionmentioning
confidence: 99%